Electrolyte‐induced modulation of electronic transport in the presence of surface charge impurities on bilayer graphene. Issue 9 (26th May 2017) - Akram, Khush Bakhat; Hassan, Muhammad Umair; Karim, Altaf; Mehmood, Mazhar; Rafiq, Muhammad Aftab; Sabahat, Sana; Manzoor, Sadia
Abstract : Transport properties of liquid electrolyte‐gated bilayer graphene (BLG) were investigated in the presence of scattering centers introduced post‐growth. The scattering centers were realized by spin‐deposition of phosphine stabilized gold nanoparticles (AuNPs) of different molar concentrations (10, 20, 30, and 40 nM) directly on top of the BLG surface. Electronic transport in such samples exhibits a cluster‐like scattering behavior, that is, a decrease in charge carrier mobility accompanied by a shift of the Dirac point toward negative values with increasing density of scattering centers, indicating the n‐type doping of graphene by AuNPs. The characteristic resistivity‐gate voltage curves show the possibility of anti‐ambipolar behavior of such gated BLG films. Drude model based Kinetic Monte Carlo (KMC) simulations agree with our experimental findings and theoretically predicted behavior. Our results support the possibility of a charge carrier modulation of graphene via foreign impurity scattering introduced on its surface, as well as by the means of large electrostatic fields obtained via the liquid electrolyte gating.